A Systematic Review of Psychological Factors Contributing to Successful English Learning - Khafshoh, Adira Lizaria; Nadhifah, Siti; Widiati, Utami (Jurnal Pendidikan Humaniora, 2023)
Psychological factors play a significant role and have potential impact on the language learning process. There are diverse perspectives due to the complexity of psychological factors that have been explored by many scholars. Combining systematic literature review and thematic analysis as well as PRISMA protocol in synthesizing and analyzing the data, this study aimed to identify psychological factors and the predominant psychological factors contributing to successful English learning in EFL context through examining the recent studies. There are several psychological factors based on the findings which are enjoyment, anxiety, self-esteem, intelligence, motivation, interest, emotion, attitude, fear of mistakes, shyness, self-efficacy, trait emotional intelligence, unhealthy environment, fear of negative evaluation, relationship with peers and teachers, confidence, critical thinking, social pressure, self-criticism, and avoidance behavior. This study found that the predominant psychological factors are motivation and anxiety. This systematic literature review will contribute to developing more effective and supportive learning environments by providing the systematic classification of psychological factors.